MENELISIK KONSEP BID’AH DALAM PERSPEKTIF HADIS - Araby, Muhammad (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
In a hadith, Prophet Muhammad Saw said, ?every bid?ah is a going astray.? Some people understand that the bid?ah in the hadith is anything new in Islam which is never done by the Prophet. This paper attempts to probe the concept of bid?ah in the hadith. After searching several books of hadiths, apparently there are some cases that occurred during the period companions of the Prophet and afterwards in which showing the companion?s creativity in worship, but the worship (practice) has never been done by the Prophet and had never been ordered to do. Nevertheless, the Prophet accepted it and gave it high appreciation since the new things were in accordance to Islamic teachings. On the other hand, there was also something new in religious matters conducted by some companions. Because it contradicts the teachings of Islam, the Prophet refused and banned it.